Acquisition of Acehnese Language Phonemes in 2-4 Year Old Children - Bungsu Keumala Sari; Istiqamah; Asriani; Devi Srinita; Khairul Amra (IKIP Siliwangi, 2024)
The aims of this research are; 1) Describe the theory of acquiring the Acehnese language in children aged 2-4 years, 2) Describe the process of acquiring the Acehnese language in children aged 2-4 years. This research was conducted using a qualitative approach with a phenomenological type. The subjects of this research were 2 children aged 2-4 years, the first child from Gampong Meunasah Mampree, Syamtalira Aron District, North Aceh Regency, and the second child from Gampong Blang, Tanah Pasir District, North Aceh Regency. Data collection techniques use observation and question and answer. The data obtained was then compiled in the form of observation field notes and questions and answers for children aged 2-4 years which were then analyzed to determine the acquisition of Acehnese language phonemes used by children aged 2 years in their daily lives. Based on the research results, it can be concluded that the language acquisition of Muhammad Aksan Rafassya aged 3 years is very good. The research subjects had mastered vowel and consonant sounds. At the age of 2 years Aksan was able to own and master words in his surroundings. This is also strengthened by mastery of nouns, adjectives and verbs. Meanwhile, Hidayatul Azizi's language acquisition at the age of 2 years is not good because he is not yet very fluent in pronouncing consonant sounds. However, at the age of 2 years Hidayatul Azizi was able to pronounce vowel sounds well. The vowel sounds that Hidayatul Azizi already pronounces fluently are the words 'jeut', 'loen', and the word 'itek'.